2001
DOI: 10.1016/s0960-9822(01)00447-x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-phosphate is generated in phagosomal membranes

Abstract: Phagocytic cells such as neutrophils and macrophages engulf and destroy invading microorganisms. After internalization, material captured within the phagosomal membrane is destroyed by a complex process of coordinated delivery of digestive enzymes and reactive oxygen species. Several endosomal, lysosomal, and oxidase components expected to participate in these events have recently been shown to bind PtdIns3P, suggesting that this lipid may play a role in this process. We used live, digital fluorescence imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
147
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(163 citation statements)
references
References 20 publications
13
147
1
2
Order By: Relevance
“…This phenomenon is not observed constantly (Յ10%), but it occurred only occasionally when followed by time-lapsed photography ( Figure 2A and Supplemental Video 1). We then used GFP-p40 phox (PX) for further studies, because it was reported to bind specifically to PI(3)P. Consistent with a previous report (Ellson et al, 2001a), GFP-p40 phox (PX) is localized faintly in the cytoplasm and predominantly on vesicular structures ( Figure 2B), which could be colabeled with antibodies against early endosomal antigen (EEA)-1 ( Figure 2C), a marker of the early endosome that is enriched in PI(3)P (Gillooly et al, 2000) ( Figure 2B). The vesicular structures and free-form of GFP-p40 phox (PX) seems to fuse readily with phagosomes in later stages of Fc␥R-mediated phagocytosis, after the phagosome is sealed ( Figure 2B and Supplemental Video 2).…”
Section: Accumulation Of P40 Phox (Px) At the Phagosome During Fc␥r-msupporting
confidence: 67%
See 2 more Smart Citations
“…This phenomenon is not observed constantly (Յ10%), but it occurred only occasionally when followed by time-lapsed photography ( Figure 2A and Supplemental Video 1). We then used GFP-p40 phox (PX) for further studies, because it was reported to bind specifically to PI(3)P. Consistent with a previous report (Ellson et al, 2001a), GFP-p40 phox (PX) is localized faintly in the cytoplasm and predominantly on vesicular structures ( Figure 2B), which could be colabeled with antibodies against early endosomal antigen (EEA)-1 ( Figure 2C), a marker of the early endosome that is enriched in PI(3)P (Gillooly et al, 2000) ( Figure 2B). The vesicular structures and free-form of GFP-p40 phox (PX) seems to fuse readily with phagosomes in later stages of Fc␥R-mediated phagocytosis, after the phagosome is sealed ( Figure 2B and Supplemental Video 2).…”
Section: Accumulation Of P40 Phox (Px) At the Phagosome During Fc␥r-msupporting
confidence: 67%
“…However, Nox2 activity can be reconstituted in vitro in the absence of p47 phox , when p67 phox and Rac1 are provided in excess (Freeman and Lambeth, 1996;Koshkin et al, 1996) or when p67 phox is adapted with the membrane-binding sequences from Rac1, although GTP-bound Rac is still required for oxidase activation (Gorzalczany et al, 2000;Alloul et al, 2001), indicating p67 phox and Rac1 are minimum essential cytoplasmic components in the Nox2 system. p40 phox also has a PX domain that specifically binds to phosphatidylinositol 3-phosphate [PI(3)P] (Bravo et al, 2001;Kanai et al, 2001), a phospholipid enriched in the early endosome (Gillooly et al, 2000) and produced in the phagosomal membrane during phagocytosis (Ellson et al, 2001a;Gillooly et al, 2001). Thus, p40 phox is also thought to serve as an adaptor component that recruits p67 phox to phagosomal membranes (Kuribayashi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clathrin binding enhanced the affinity of AP2 for internalization signals to a similar extent, but the effect of clathrin and PtdIns(3)P were not additive (286). However, when fluorescent proteins that bind PtdIns(3)P are expressed in cells, they label endosomes and not the plasma membrane (32,92,318), suggesting that there is little free PtdIns(3)P at the cell surface. There is a recent report that PtdIns3KIIC2␣ localizes to the nucleus rather than the plasma membrane (77).…”
Section: Ptdins3kiic2␣mentioning
confidence: 96%
“…At higher expression levels, they will interfere with the normal regulation of PIP production. With these limitations in mind, PtdIns(3)P has been detected primarily on endocytic membranes (32,92,318), PtdIns(4,5)P 2 at the plasma membrane (148,149,219,234,365) and on internal membranes enriched in lipid rafts (27,297), and PtdIns(4)P on the Golgi (13,201,372). PtdIns4K activity has been detected in cell fractions enriched in lysosomes (7,54,56).…”
Section: Proteins Containing Enth/anth Domains Thought To Function Inmentioning
confidence: 99%